MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA SMP KELAS VII PADA MATERI HIMPUNAN DENGAN MENGGUNAKAN PENDEKATAN PROBLEM BASED LEARNING - Lisnawati Lisnawati; Ika Wahyu Anita (IKIP Siliwangi, 2022)
This study aims to increase the motivation to learn mathematics in the set material by using a problem based-learning approach. This type of research is classroom action research (CAR) using the design of the classroom action research model (CAR) created by Kemmis and Mc Taggart. The subjects of this study were 10th graders at SMPN 1 Margaasih. The data collection technique used a learning motivation questionnaire with 5 indicators and 10 statements, each with 5 positive and negative statements. The results of this study indicate an increase in students' learning motivation in each cycle with a good to very good category. The use of problem based learning approach is proven to be able to increase students' learning motivation.